Iranian psychiatrists’ attitude towards clozapine use for patients with treatment-resistant schizophrenia: a nationwide survey - Leeba Rezaie; Azadeh Nazari; Roya Safari-Faramani; Shamarina Shohaimi; Habibolah Khazaie (BMC Psychiatry, 2022)
Abstract Background Clozapine has the greatest efficacy for treatment-resistant schizophrenia (TRS), even though its underutilization is not uncommon across different countries. This study aimed to investigate the knowledge and attitude of Iranian psychiatrists toward clozapine use. Method In this cross-sectional study, a questionnaire was distributed among psychiatrists registered with the Iranian Psychiatrists Association (including its provincial branches) to assess their knowledge and attitude towards clozapine use. A total of 282 psychiatrists completed the questionnaire. Descriptive analysis was used to describe demographic information, and Chi-square tests were conducted to determine if there is an association between academic position and work experience. All statistical analyses were performed using SPSS® version 25.0 for Windows, and a significance level of 0.05 was used. Results Most respondents (93%) acknowledged that they prescribed clozapine for their patients, and 74% believed that clozapine was more effective than other antipsychotic drugs. However, 43.3% of the respondents said they did not believe in the safety of clozapine. Difficulty initiating and having no firsthand experience in the superiority of clozapine were reported by 81.2 and 80% of the respondents, respectively. Our results also showed an association between having an academic position and access to appropriate facilities for the control and management of patients treated with clozapine and believing in the safety of clozapine (p < 0.05). Longer work experience (more than 15 years) was associated with a higher prescription of clozapine, belief in greater effectiveness of clozapine, and its safety (p < 0.0001). Conclusion Iranian psychiatrists had a good self-perception of knowledge about the efficacy of clozapine for patients with TRS, but concerns about serious side effects are common. Psychiatrists with longer work experience and academic positions were more optimistic towards clozapine use than the younger ones with no academic position. Considering the results in planning the strategies to decrease concerns about clozapine use is recommended.